2021
DOI: 10.1002/joc.7316
|View full text |Cite
|
Sign up to set email alerts
|

Identifying meaningful covariates that can improve the interpolation of monsoon rainfall in a low‐lying tropical region

Abstract: The assessment of spatio‐temporal distribution of rainfall over the entire monsoon season is critical for the water resources management in a tropical low‐lying region like Bangladesh. The primary objective is to find suitable interpolation methods for each monsoon month as well as the accumulated rainfall for the entire season in Bangladesh. As the unique position of Bangladesh and monsoon system both contribute the variation in rainfall, the identification of associated suitable covariates can offer reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…in which i z denotes the known value of variable z at a site i, N denotes the number of neighbor stations, i d is the Euclidean distance from site i to ungauged site, and p is a control parameter. Following the recommendations of Pellicone et al (2018) and Das and Wahiduzzaman (2022), we have adopted a value of 2 for parameter p, which entails a larger weight to nearby sites in the interpolation procedure.…”
Section: ( )mentioning
confidence: 99%
See 2 more Smart Citations
“…in which i z denotes the known value of variable z at a site i, N denotes the number of neighbor stations, i d is the Euclidean distance from site i to ungauged site, and p is a control parameter. Following the recommendations of Pellicone et al (2018) and Das and Wahiduzzaman (2022), we have adopted a value of 2 for parameter p, which entails a larger weight to nearby sites in the interpolation procedure.…”
Section: ( )mentioning
confidence: 99%
“…For the spatialization of the quantiles, both the IDW method and ordinary kriging were considered, as suggested by Das and Wahiduzzaman (2022), for comparison. The ordinary kriging, which is based on a continuous Gaussian field with covariance function materialized by semivariograms, is the most common kriging method (Carvalho & Vieira, 2001;Libertino et al, 2018).…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have found that just the assimilation of several parameters does not provide highly accurate and robust GWP maps; therefore, to achieve the accurate GWP maps, researchers have to use different methods, which can assimilate mathematically all parameters having different data patterns and direction (Hembram et al 2019;Das et al 2021). Therefore, researchers have been paid higher interest in developing such accurate GWP modeling methods (Nguyen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we classified all methods as per their operational background, such as (1) statistical approaches for zoning groundwater potential, which have a long history of use (Mallick et al 2021c;Pham et al 2021). Statistical procedures that are now in use include frequency ratio (Abd Manap et al 2014;Guru et al 2017), logistic regression (Rizeei et al 2019), weight of evidence (Rane and Jayaraj 2021;Das et al 2021), certainty factor (Razandi et al 2015), and evidential belief function (Tahmassebipoor et al 2016). However, they have several disadvantages, including a lack of precision (Chen et al 2020).…”
Section: Introductionmentioning
confidence: 99%